Why the West rules-- for now the patterns of history, and what they reveal about the future - Morris, Ian. (New York Straus and Giroux, 2010)
In the middle of the eighteenth century, British entrepreneurs unleashed the astounding energies of steam and coal and the world changed forever. Factories, railways and gunboats then propelled the West's rise to power, and computers and nuclear weapons in the twentieth century secured its global supremacy. Today, however, many worry that the emergence of China and India spell the end of the West as a superpower.
Includes bibliographical references (p. [679]-723) and index.
Keywords: Civilization, Western